Fertilisation system influence on the main agrochemical indicators of soil and productivity of white cabbage - Oleksandr Kuts; Vasyl Kokoiko; Volodymyr Mykhailyn; Yuriy Syromyatnikov; Olga Zhernova (Наукові горизонти, 2023)
The research relevance is determined by the need to study the long-term use of various fertilisers and their effect on the soil nutrient regime, yield, and quality of white cabbage. The research aims to determine the effect of different nutrition optimisation systems on the yield and quality of late-ripening white cabbage in irrigated vegetable-fodder crop rotation. Field, statistical, calculation-analytical and laboratory methods were used to conduct the research. It was established that the use of a mineral fertilizer system (N550P260K370 + “NutriVant Plus Universal”) led to an increase in the level of supply of the topsoil with mobile nitrogen, phosphorus, and potassium compounds, and had a positive effect on the biometric parameters and productivity of white cabbage plants. All fertilisation systems, except for the application of microbial preparations only provided a significant increase in yields in the range of 21.6-71.8%. However, a significant increase in the content of vitamin C in cabbage heads was observed for all fertilisation systems studied, except for the use of 40-60 t/ha of manure + N60P60K45 та N550P260K370 + “NutriVant Plus Universal”. The nitrate content in the heads did not increase significantly after fertilisation. The ineffectiveness of using the system of microbial preparations, including seed treatment with Azotobacter chroococcum, and soil treatment before pre-sowing cultivation with Roundfix, to optimise the nutrition of white cabbage plants was noted. (Paenibacillus polymyxa, Bacillus megaterium var. phosphaticum, Enterobacter, Azotobacter chroococcum, Bacillus subtilis) and five foliar fertilisers Organic Balance (Bacillus subtilis, Azotobacter chroococcum, Paenibacillus polymyxa). The practical value is determined by obtaining results for adjusting fertiliser doses when planning their application in crop rotations of farms of different forms of ownership